2020
DOI: 10.1590/1679-78255754
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-based calibration of main Brazilian structural design codes

Abstract: Structural reliability theory has long been recognized as the proper tool to guide selection of partial safety factors in limit state structural design codes. Brazilian design codes, however, have never been through this calibration process. This paper addresses the reliability-based calibration of partial safety factors of Brazilian design codes for loads (NBR8681:2003), and for steel (NBR8800:2008) and concrete (NBR6118:2014) structures. The study is based on an extensive dataset of load and strength variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
(38 reference statements)
2
20
1
Order By: Relevance
“…The few existent reliability assessments for structures in Brazil (Beck and Souza Júnior [32]; Santos et al [33],) demonstrated annual failure probabilities ranging from -4 2.15 × 10 to -8 6.80 × 10 , encompassing the two target values adopted herein. Recent reliability-based calibration studies for the Brazilian codes ( [32]; Santiago et al [34]; Santiago et al [35],) adopted -5 2.7 × 10 for the target annual failure probability, which is in fair agreement with the lower bound investigated in this paper. The inferior bound is also consistent with international standards for acceptable individual risk of fatality due to structural failure, a probability of -6 10 per year for low seismicity regions [11].…”
Section: Risk-targeting Methodologysupporting
confidence: 85%
“…The few existent reliability assessments for structures in Brazil (Beck and Souza Júnior [32]; Santos et al [33],) demonstrated annual failure probabilities ranging from -4 2.15 × 10 to -8 6.80 × 10 , encompassing the two target values adopted herein. Recent reliability-based calibration studies for the Brazilian codes ( [32]; Santiago et al [34]; Santiago et al [35],) adopted -5 2.7 × 10 for the target annual failure probability, which is in fair agreement with the lower bound investigated in this paper. The inferior bound is also consistent with international standards for acceptable individual risk of fatality due to structural failure, a probability of -6 10 per year for low seismicity regions [11].…”
Section: Risk-targeting Methodologysupporting
confidence: 85%
“…where Φ(•) is the cumulative distribution function of the standard normal distribution; 𝛼𝛼 𝑆𝑆 is the FORM sensitivity factor for the action effects, and 𝛽𝛽 𝑇𝑇 is the target reliability index. In Section 3.6, the reliability-based calibration of partial safety factors employed in Brazilian design codes for steel [45] and concrete [46] structures -originally performed by Santiago et al [47] -is re-processed using the live load statistics developed herein, and the mean reliability index using current NBRs 8681, 8800 and 6118 factors is found to be equal to 3.17 for a period of 50 years. Hence, a target reliability index of 𝛽𝛽 𝑇𝑇 = 3.17 is considered herein.…”
Section: Partial Safety Factor For Uls Verificationmentioning
confidence: 99%
“…Yet, the analysis is justified as we are more interested in the variation of reliability indexes for different points of the structure. Moreover, the recent study on reliability-based calibration of Brazilian design codes [49] has suggested that the partial load factor for dead load should be reduced (to ). These values are somewhat closer to the values given by ASCE 7, as reported below.…”
Section: Load Combinations and Designmentioning
confidence: 99%